Brassicaceae Mustards: Traditional and Agronomic Uses in Australia and New Zealand - Rahman, Mahmudur (Molecules, 2018)
Commonly cultivated Brassicaceae mustards, namely garlic mustard (Alliaria petiolata), white mustard (Brassica alba), Ethiopian mustard (B. carinata), Asian mustard (B. juncea), oilseed rape (B. napus), black mustard (B. nigra), rapeseed (B. rapa), white ball mustard (Calepina irregularis), ball mustard (Neslia paniculata), treacle mustard (Erysimum repandum), hedge mustard (Sisymbrium officinale), Asian hedge mustard (S. orientale), smooth mustard (S. erysimoides) and canola are the major economically important oilseed crops in many countries. Mustards were naturalized to Australia and New Zealand and Australia is currently the second largest exporter of Brassicaceae oilseeds to meet the global demand for a healthy plant-derived oil, high in polyunsaturated fats. Apart from providing edible oil, various parts of these plants and many of their phytochemicals have been used traditionally for both agronomic as well as medicinal purposes, with evidence of their use by early Australian and New Zealand settlers and also the indigenous population. This review provides an overview of the current knowledge of traditional and agronomic uses of Brassicaceae oilseeds and mustards with a focus on their importance in Australia and New Zealand.